KARYOTYPE OF THE FRESHWATER FISH THORICHTHYS HELLERI (PISCES: CICHLIDAE) - Hernández-Guzmán, Javier (2015)
Ten specimens of Thorichthys helleri (five females and five males) were collected in a lagoon ofthe town from Paraiso, Tabasco, Mexico. Conventional cytogenetic technique was applied toorgan tissues (pancreas and kidney) and peripheral blood. Cytogenetic study on T. helleri revealed a karyotype of 2n=48 chromosomes which is described; chromosome classification corresponded to 2 metacentric-submetacentric + 44 subtelocentric-telocentric + 2 sex chromosome (1 msm + 1 stt). The fundamental number in T. helleri was NF=51. The karyotype of T. helleri from Paraiso, Tabasco, Mexico, is different from 19 other species of the cichlid family.It contributes unpublished biological information on T. helleri with distribution in Southern of Mexico.